Sikap Siswa Terhadap IPA berdasarkan Investigasi dan Korelasi: Kesenangan Belajar dan Minat Meluangkan Waktu pada IPA : The Student's Attitude toward Science based on Investigation and Correlation: Learning Fun & Enthusiasm for Spending Time - Kurniawan, Dwi Agus; Astalini, Astalini; Kurniawan, Nugroho; Anggraini, Lika (SEJ (Science Education Journal), 2019)
This study purposed to investigate attitudes towards science in junior high school students, based on 2 attitude indicators: (1) enjoyment in science lesson & (2) leisure interest in science. In addition, measurements were also made regarding the relationship between the two indicators of attitude. This research is survey research. The results of the data came from an attitude questionnaire consisting of indicators (1) enjoyment in science lesson and (2) leisure interest in science. The sample consisted of 2815 junior high school students in Jambi Province, Indonesia. The results showed that for indicators: (1) enjoyment in science is good category with a percentage of 48.1%, (2) leisure interest in science is fairly good category with a value: 47.2% and This indicator leads to a positive trend supported by a positive attitude with a greater good value: 38.4%, while for the analysis of the correlation between the two indicators shows a positive correlation with a sig: 0,000 (<0.05) and has a strong degree of correlation indicated by the value "Pearson Correlation": 0.716. Therefore, it is concluded overall attitudes towards science at Junior high school students in Jambi, Indonesia have a positive attitude and are categorized well.